Hypothermic Machine Perfusion Reduced Inflammatory Reaction by Downregulating the Expression of Matrix Metalloproteinase 9 in a Reperfusion Model of Donation After Cardiac Death. Issue 6 (27th January 2016) - Fu, Zhen; Ye, Qifa; Zhang, Yang; Zhong, Zibiao; Xiong, Yan; Wang, Yanfeng; Hu, Long; Wang, Wei; Huang, Wei; Ko, Dicken Shiu‐Chung
Abstract: The exact mechanism by which hypothermic machine perfusion (HMP) improves the graft quality in kidney transplantation of donation after cardiac death (DCD) remains unclear. The aim of this study was to investigate the correlation between the expression of matrix metalloproteinase 9 (MMP‐9) and inflammatory reaction in kidney ischemia‐reperfusion (I/R) injury injury followed by cold storage (CS) or HMP model of DCD. New Zealand white rabbit kidneys were subjected to 35 min of warm ischemia and 1 h reperfusion, then preserved by either 1 h reperfusion (sham‐operated group), 4 h CS or 4 h HMP in vivo. Kidneys were reperfused 24 h followed by further analysis. No treatment was given to rabbits in the normal control group. The expression of MMP‐9, nuclear factor‐κB (NF‐κB), and MMP‐2 mRNA were detected by real‐time PCR (RT‐PCR). MMP‐9 was located by immunohistochemistry and immunofluorescence methods. Tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), myeloperoxidase (MPO), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured by kits for each groups. Compared with the CS group, the expression of MMP‐9 and NF‐κB mRNA were downregulated in HMP group ( P  < 0.05). In contrast, expression of MMP‐2 mRNA had no statistical significance between CS group and HMP group ( P  > 0.05). In normal control and sham‐operated groups, a low level of MMP‐9 expression was detected in glomeruli. However, positive signals of MMP‐9 were mostly located in the tubulointerstitium and the vascular wall of CS and HMP groups. Expression of TNF‐α, IL‐6, MDA, and activity of MPO decreased while activity of SOD in the HMP group increased in contrast to the CS group ( P  < 0.05). In conclusion, inflammatory cytokines mediated MMP‐9 expression through NF‐κB band to MMP‐9 promoter region, resulting in renal injury. Therefore, HMP reduced inflammatory reaction by downregulating the expression of MMP‐9, which may be the mechanism of kidney protection in I/R injury.